2016
DOI: 10.1152/japplphysiol.00685.2015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cooling after acute hyperthermia alters intestinal morphology and increases the systemic inflammatory response in pigs

Abstract: The study objective was to determine the direct effects of rapid cooling after acute hyperthermia on intestinal morphology and inflammatory response in pigs. In four repetitions, male pigs (N = 36; 88.7 ± 1.6 kg) were exposed to thermoneutrality (TN; n = 3/rep; 19.5 ± 0.1°C) for 6 h or heat stress (HS; 36.4 ± 0.1°C) for 3 h, followed by a 3-h recovery period of rapid cooling (HSRC; n = 3/rep; rapid TN exposure and ice water dousing for 1.5 h) or gradual cooling (HSGC; n = 3/rep; gradual decrease from HS to TN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 49 publications
(86 reference statements)
4
23
6
Order By: Relevance
“…This ischemic insult aggravates intestinal damage and dysfunction of the intestinal barrier. As reported in previous studies ( 25 , 34 ), the results of the present study showed that intestinal damage was aggravated following cooling treatment. This may result from gut reperfusion during the cooling treatment and the sustained systemic inflammatory cascade ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 89%
“…This ischemic insult aggravates intestinal damage and dysfunction of the intestinal barrier. As reported in previous studies ( 25 , 34 ), the results of the present study showed that intestinal damage was aggravated following cooling treatment. This may result from gut reperfusion during the cooling treatment and the sustained systemic inflammatory cascade ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 89%
“…Hyperthermia causes an increase in intestinal damage due to ischemic injury (Arieli et al, 2003) and hypoxia (Horowitz, 2007) resulting in greater permeability and endotoxin translocation (Lambert, 2009;Johnson et al, 2016) and morphological alterations such as reduced villus height and crypt depth, and a reduction in the villus height to crypt depth ratio (Pearce et al, 2013a; Johnson et al, 2016).…”
Section: Daymentioning
confidence: 99%
“…Indeed, basing treatment strategies on that index alone might inadvertently expose hyperthermic humans to unforeseen complications. For instance, Johnson, Sapkota, and Lay () investigated the impact of rapidly (ice‐cold water douche; 4°C) and gradually cooling (staged air cooling to 20.7°C) hyperthermic pigs. Faster rectal temperature reductions accompanied the rapid cooling, with animals experiencing higher circulating endotoxin concentrations (lipopolysaccharide) than either the gradually cooled or normothermic pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the optimal manner in which cooling might be achieved has been debated (Casa, Kenny, & Taylor, 2010), with some recommending ice-cold water immersion Binkley, Beckett, Casa, Kleiner, & Plummer, 2002;Casa et al, 2007), a method first advocated by Ferris, Blankenhorn, Robinson, and Cullen (1938), whereas others advocate less aggressive cooling strategies (Caldwell et al, 2009;Taylor, Caldwell, van den Heuvel, & Patterson, 2008a;Weiner & Khogali, 1980;Wyndham et al, 1959). One aspect of the former approach is the possibility of exposure to adverse, cold-induced pathophysiological sequelae, including cardiac arrhythmia, reduced cerebral blood flow, hypertension and endotoxaemia (Johnson et al, 2016;Mantoni, Belhage, Pedersen, & Pott, 2007;Shattock & Tipton, 2012;Tipton, 1989).…”
Section: Introductionmentioning
confidence: 99%